A study of efficacy and safety of intravenous iron sucrose for the treatment of moderate anaemia in antenatal women in South India - Vundi, Venkata Ramana; Pudutha, Madhavi; Kambar, Chandrakala (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Iron deficiency anaemia in pregnancy is a common medical problem throughout India with the burden of disease impacting on both mother and the newborn. The WHO technical group working on the prevention and treatment of anaemia has documented that parenteral iron therapy has produced a rapid and better correction of iron deficiency anaemia. Methods: A total of 61 antenatal women in the age group of 18-25yrs were enrolled and randomly assigned into study group. For a period of 4 weeks, study group received iron sucrose intravenously. The results were noted, tabulated, analysed and expressed as descriptive statistics. Student's ‘t’ test and percentages were compared using chi square test. P -value, <0.001 was considered significant. The results were analysed by using SPSS V-21 software. Results: Mean rise of Hb was 2.51±0.44 with IV iron sucrose this was highly significant (HS). Mean rise of MCV was 8.02±6.72 with IV iron sucrose this was not significant (NS). Mean rise of PCV was5.7±2.77 with IV iron sucrose. These findings showed improvement in Hb and PCV which were statistically highly significant (HS). Adverse effects were 14% in the group. Conclusions: The present study proved that iron sucrose when given intravenously there was a rapid improvement in anaemia. IV iron sucrose was proved to be safe with minimal side effects.